Study of the course of inferior epigastric artery with reference to laparoscopic portal - Rao, Manvikar Purushottam (Medknow Publications & Media Pvt Ltd, 2013)
INTRODUCTION: Laparoscopy has been in vogue for more than 2 decades. Making portals in the anterior abdominal wall for introducing laparoscopic instruments is done with trocar and cannula which is a blind procedure. Stab incision and trocar insertion, though safe, at times can lead to injury of blood vessels of anterior abdominal wall more so the inferior epigastric artery (IEA). Trauma to abdominal wall vessels is 0.2%-2% of laparoscopic procedures and said to be 3 per 1000 cases. Injury to IEA is one of the commonest complications seen. Purpose of the present study was to observe the course of IEA in 50 formalin preserved cadavers, by dissection. MATERIALS AND METHODS: In 50 formalin fixed cadavers, IEA was exposed by opening the rectus sheath. Rectus was divided and IEA was exposed. Five reference points A, B, C, D, and E were defined. A was at pubic symphysis, while E at umbilicus. B, C, and D were marked at the distance of 3.5, 7, and 10.5 cm, respectively from pubic symphysis. Distances of the IEA from these midline points were measured with the help of sliding vernier calipers. RESULTS: Significant observation was variations in the length of IEA. It was seen to end at a lower level than normal (three cases on right and four on left side) by piercing rectus. In 14, cadavers artery did not reach up to umbilicus on both sides. Nearest point of entry of IEA in to rectus sheath at the level of pubic symphysis was 1.2 cm on left and 3.2 cm on right side. Farthest point from point A was 6.8 cm on right and 6.9 cm on left side. Width of strip of abdominal wall which was likely to have IEA beneath was up to 4 cm till level C and beyond which it widened up to 5cm on left side and 6 cm on right at umbilicus. DISCUSSION: Present study did reveal notable variations in length and termination of IEA. No uniformity in entry of IEA in to the rectus sheath was observed. Findings did concur with earlier observations but the strip of skin of arterial zone was not equidistant from midline but had moved more medially on left side. Medial limit of this safety zone found to be lesser than 2 cm on left side. However, the lateral limit of the zone was within 7.5 cm. Additional variation was strip of abdominal wall likely to have IEA beneath was up to 4 cm till level C and had diverging limits beyond C. IEA was more notorious in its course. These variations prompt for a preoperative mapping of IEA and thus a useful step in preoperative protocol.